Evolution of lattice dynamics in ferroelectric hexagonal REInO3 (RE = Ho, Dy, Tb, Gd, Eu, Sm) perovskites. (29th July 2016) - Paul, Barnita; Chatterjee, Swastika; Gop, Sumana; Roy, Anushree; Grover, Vinita; Shukla, Rakesh; Tyagi, A K
Abstract: Rare-earth indates emerge as one of the efficient geometric ferroelectric materials, in which the spontaneous polarization can be tuned by varying their crystal structure along the 4 f rare-earth series. We report a systematic study of structural changes in hexagonal REInO3 perovskite (RE = Ho 3+, Dy 3+, Tb 3+, Gd 3+, Eu 3+, Sm 3+ ) and YInO3 of P 63 cm space group by powder x-ray diffraction (XRD) and Raman scattering measurements. The crystal structure of these materials could be investigated by the Rietveld refinement of their XRD patterns. We have calculated density of states of phonons using density functional theory and examined the atomic displacements corresponding to observed Raman modes. The evolution of lattice dynamics of REInO3 has been probed by correlating various Raman modes with the structural distortion of the unit cell and the characteristics of the rare-earth ions. We report the appearance of the coupled mode in the phonon spectra. We have estimated spontaneous polarization from the structural distortion in this system and shown that it can be modulated by varying RE 3+ ions in REInO3 . We also report the appearance of a ferroelectric soft Raman mode, a unique characteristic of these materials.